Aligned channel Gelatin@nanoGraphite aerogel supported form-stable phase change materials for solar-thermal energy conversion and storage. (5th January 2023) - Feng, Jian; Liu, Xianjie; Lin, Fankai; Duan, Shengzhi; Zeng, Keqing; Bai, Yaning; Wu, Xiaowen; Huang, Zhaohui; Min, Xin
Abstract: To overcome the poor shape stability, low thermal conductivity, and weak photo response of phase change materials (PCMs), we designed a kind of Gelatin@nanoGraphite aerogel with aligned channel structure of graphite nanosheets and a new type of stable Paraffin/Gelatin@nanoGraphite composite PCMs was fabricated in this work. The graphite nanosheets were used as thermal conduction and photon absorption fillers. The microstructure, thermal conductivity, thermal stability, and solar-thermal conversion of the composite PCMs have been investigated. The results show that the rich porosity of the prepared Gelatin@nanoGraphite aerogel effectively loads a large amount of paraffin wax (>93.2 wt%). Meanwhile, the composite PCMs had anisotropic solar-thermal conversion and thermal conductivity (radial 3.75 and axial 2.59 W/(m·K)), high melting enthalpy (>146.4 J/g), and excellent phase change cycle and shape stability. This material has intensive application prospects in the fields of building energy saving, human body hyperthermia and solar energy collection system. Graphical abstract: Paraffin/Gelatin@nanoGraphite PCMs with anisotropic thermal conduction capacity and solar-thermal conversion ability were prepared by directional freeze-drying process and vacuum impregnation. Image 1